Fear of Missing Out (FOMO) and Social Media Addiction on Instagram among Adolescents - Nugrahani, Rizka Fibria; Lestari, Laila Indra; Setyoningtias, Khasdyah Dwi Dewi; Aurellia, Wulan Zaesa; Achmad, Zidan (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
This study examines the influence of Fear of Missing Out (FoMO) on Instagram Addiction among adolescents in the context of the rapid development of the internet and social media. The internet, especially Instagram, has become very popular among adolescents, providing convenience and creativity but also triggering FoMO, which is defined as the anxiety of missing out on other people's experiences. Quantitative methods were used using regression analysis with FoMO as a predictor and Instagram Addiction as the dependent variable. The ANOVA results showed that the regression model was significant (F = 15.210, p < 0.001), while the regression coefficient indicated a positive effect of FoMO on Instagram Addiction (B = 0.005, p < 0.001). These findings indicate that every one-point increase in FoMO corresponds to a 0.005-point increase in Instagram Addiction (logIG). In conclusion, FoMO is a significant predictor of Instagram Addiction, implying that higher levels of FoMO increase the likelihood of addictive behavior on Instagram, underscoring the importance of addressing FoMO in understanding adolescent digital behavior.